Association of inflammation-related markers and diabetic retinopathy severity in the aqueous humor, but not serum of type 2 diabetic patients. - Lucia Saucedo; Isabel B Pfister; Christin Schild; Justus G Garweg (PLoS ONE, 2023)
Diabetic retinopathy (DR) is a frequent microvascular complication of diabetes mellitus, and inflammatory pathways have been linked to its pathogenesis. In this retrospective, observational pilot study, we aimed to compare the concentrations of four inflammation-related proteins, ZAG, Reg-3a, elafin and RBP-4, in the serum and aqueous humor of healthy controls and diabetic patients with different stages of DR. The concentrations of VEGF-A, IL-8, IL-6 were determined in parallel as internal controls. In the serum, we did not find significant differences in the concentrations of target proteins. In the aqueous humor, higher levels of ZAG, RBP-4, Reg-3a and elafin were observed in advanced nonproliferative DR (NPDR)/ proliferative DR (PDR) compared to controls. The levels of ZAG and RBP-4 were also higher in advanced NPDR/PDR than in nonapparent DR. Normalization of target protein concentrations to the aqueous humor total protein demonstrates that a spill-over from serum due to breakage of the blood-retina barrier only partially accounts for increased inflammation related markers in later stages. In conclusion, we found elevated levels of Reg-3a, RBP-4, elafin and ZAG in advanced stages of diabetic retinopathy. Higher levels of pro-inflammatory proteins, Reg-3a and RBP-4, might contribute to the pathogenesis of diabetic retinopathy, as the parallel increased concentrations of anti-inflammatory molecules elafin and ZAG might indicate a compensatory mechanism.